Monks, Blogs and Three Media Cases: Russian-Speaking Buddhist Communities in the Era of Social Media - Ostrovskaya, Elena (Religions, 2024)
This paper focuses on the problem of how Buddhism was reinstitutionalized in Russia in the frame of the meta process of mediatization. The empirical part of this study included two stages and was conducted during 2020–2024. In this paper, the authors focused mainly on the peculiarities of constructing strategies in the Internet and new media via traditional Gelug ethnic offline organizations, the Russian branches of the International Karma Kagyu Community, International Dzogchen Community and Russian-speaking community of Theravada converts. The methodological framework of the research included the institutional perspective developed by the Danish media scholar Stig Hjarvard for studying the mediatization of religion and the concept of “mediatized public religion” by Mia Lövheim and Marta Axner, as well as the concept of “digital religious innovators” by Heidi Campbell. The authors revealed that the processes of digitalization and mediatization have resulted in the emergence of Russian mediatized Buddhism. Various trends in modern Russian Buddhism are disproportionally represented in the public sphere of media; representation directly correlates with the strategies that Digital Buddhist creatives of different streams—Gelugpa traditional, Dzogchen, Theravada or Karma Kagyu—have chosen in relation to the Internet and new media.